Post Project Assessment of Risk in Construction Projects - Naveen, N; Harshit, Nadendla; Muthu, D; Venkatasubramaniam, C; Sharmila, P (International Journal of Engineering and Technology, 2018)
In these days construction projects are applied in risky and unstable environments results in a very high risk factors and unreliability. Risk assessment is a way to conclude the risks and quandary of the project executed and directs it with some actual solutions. In this field the top managements authority need to detect the value, phase, grade and status of the project. Since there is lot of different problems are intricate in construction and it is so hard to keep in existence of value, phase, grade and status as schedule. This paper recognizes the factors required in the projects of construction field and to predict the possibilities which are affects the construction and reduction calculations. The probable risk factors available in the post project and it is categorized the very little effects to huge effects has been composed by the questionnaire survey. And the outcomes were look over by the SPSS software. The acceptable guidance was afforded to make over the negative issues.Â Â